2015
DOI: 10.1111/jce.12751
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Tachycardia as the First‐Line Therapy in Patients With Coronary Artery Disease and Preserved Left Ventricular Systolic Function: Long‐Term Results

Abstract: Catheter ablation of VT as the first-line treatment in patients with CAD and relatively preserved LVEF is a viable strategy. It may prevent implantation of the ICD in a considerable proportion of patients. Abolition of all inducible VTs confers low VT recurrence rate over a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Numerous studies have shown CA to be effective. 23 26 , 29 33 Patel et al 30 reported on a 262 patient study comparing CA to non-ablative strategies and found the rate of recurrent VT was lower in CA populations than in the non-CA cohort. Numerous other reports have demonstrated the efficacy and potential of CA as a first-line strategy for VT. 23 , 24 , 26 , 31 33 While promising, RF CA is not without issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown CA to be effective. 23 26 , 29 33 Patel et al 30 reported on a 262 patient study comparing CA to non-ablative strategies and found the rate of recurrent VT was lower in CA populations than in the non-CA cohort. Numerous other reports have demonstrated the efficacy and potential of CA as a first-line strategy for VT. 23 , 24 , 26 , 31 33 While promising, RF CA is not without issues.…”
Section: Discussionmentioning
confidence: 99%
“…CA is designed to alter cardiac tissue architecture, thereby preventing/correcting cardiac arrhythmias, including VT. 19 CA strategies have been shown to be effective treatment options. [22][23][24][25][26][27][28] CA is typically performed using radio frequency (RF) to burn cardiac tissue, destroying an arrhythmogenic foci to create a scar resulting in conduction block, thereby preventing propagation of the arrhythmia. Numerous studies have shown CA to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients were not well represented in pivotal clinical trials on the use of ICDs. Several smaller studies including our study with 31 patients who underwent CA and ICD was implanted in 42% for continuing inducibility of non-clinical VTs, suggested that primary CA may prevent recurrences of VT and that these patients have a low risk of SCD [14]. The collaborative study by Maury et al compared the outcome of 166 patients with different type of structural heart disease, left ventricular ejection fraction over 30% and well tolerated VT who underwent CA with 378 similar subjects with an ICD during the same period [15].…”
Section: Ventricular Tachycardia In Structural Heart Diseasementioning
confidence: 92%
“…For the first time, recommendations include catheter ablation as an alternative to ICD therapy in IHD patients with haemodynamically tolerated SMVT and preserved or mildly reduced left ventricular function 71 , 72 (class IIa), while the 2015 guidelines and other international guidelines 73 recommend ICD implantation in this scenario. Although the secondary preventive ICD trials did not show a survival benefit in patients with a left ventricular ejection fraction ≥35%, 74 ICDs are frequently implanted in this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Similar evolution of recommendations can be found regarding coronary artery disease. In this context, programmed electrical stimulation (PES) experiences a renaissance: Not only is the recommendation for PES in patients with unexplained syncope and previous myocardial infarction upgraded to class I, but the new guidelines also recommend ICD therapy in patients with LVEF ≤40% and documented NSVT in whom SMVT is inducible by PES (IIa) 71 , 72 and, for the first time, recommends ICD therapy in ARVC patients with moderate right or left ventricular dysfunction and either NSVT or inducible SMVT. 81–84 PES is also mentioned (class IIb recommendation) for risk stratification in asymptomatic patients with a spontaneous type 1 Brugada ECG.…”
Section: Introductionmentioning
confidence: 99%